3-(4-Hydroxy-3-methoxyphenyl) propionic acid contributes to improved hepatic lipid metabolism via GPR41 - Ohue-Kitano, Ryuji; Masujima, Yuki; Nishikawa, Shota; Iwasa, Masayo; Nishitani, Yosuke; Kawakami, Hideaki; Kuwahara, Hiroshige; Kimura, Ikuo (Scientific reports, 2023)
3-(4-hydroxy-3-methoxyphenyl) propionic acid (HMPA) is a metabolite produced by the gut microbiota through the conversion of 4-hydroxy-3-methoxycinnamic acid (HMCA), which is a widely distributed hydroxycinnamic acid-derived metabolite found abundantly in plants. Several beneficial effects of HMPA have been suggested, such as antidiabetic properties, anticancer activities, and cognitive function improvement, in animal models and human studies. However, the intricate molecular mechanisms underlying the bioaccessibility and bioavailability profile following HMPA intake and the substantial modulation of metabolic homeostasis by HMPA require further elucidation. In this study, we effectively identified and characterized HMPA-specific GPR41 receptor, with greater affinity than HMCA. The activation of this receptor plays a crucial role in the anti-obesity effects and improvement of hepatic steatosis by stimulating the lipid catabolism pathway. For the improvement of metabolic disorders, our results provide insights into the development of functional foods, including HMPA, and preventive pharmaceuticals targeting GPR41.